Mosque architecture in Malaysia : classification of styles and possible influence - Mohamad Rasdi, Mohamad Tajuddin (Faculty of Built Environment, UTM, 2007)
The main purpose of the research is to set up an initial framework of architectural description of Muslim architecture in Malaysia within the context of the architectural concern of ‘style’. The main concern is to elucidate clearly the different architectural styles of Muslim architecture and suggest hypotheses for future studies in relation to the forces which might have been instrumental in the conception of these styles. The research is important in order to project the message that much of what we understand as ‘Islamic Architecture’ in the present literature comes from various artistic and political agendas that have questionable merits compared to an analytical approach of Islamic architecture from the Qur’an and the Sunnah of the Prophet Muhammad (peace be upon him). The research is also important for practicing architects to understand that the present syntax of ‘Islamic Architecture’ with its references in Middle Eastern, Mid Asian and African models are not necessarily the best precedence to project the architectural message of Islam. As opposed to the three classification of Traditional, Colonial and Modern styles of mosque architecture, the research has identified seven main styles with a suggestion of the rationale and influences of those styles.